Temporomandibular joint involvement in patients with juvenile idiopathic arthritis: a retrospective chart review. (3rd July 2020) - von Schuckmann, L; Klotsche, J; Suling, A; Kahl-Nieke, B; Foeldvari, I
Abstract : Objective: To study the proportion of patients with temporomandibular joint (TMJ) involvement among patients with juvenile idiopathic arthritis (JIA), as well as associated clinical characteristics and signs/symptoms. Method: We performed a retrospective chart review on consecutive patients followed in the Hamburg Centre for Paediatric and Adolescent Rheumatology Eilbek between January 2010 and July 2012. TMJ involvement was diagnosed based on clinical examination; a subgroup of patients was also assessed by magnetic resonance imaging (MRI). Results: The study included 2413 patients with JIA (52.1% girls, mean age at JIA onset 9.5 years). The most frequent JIA category was oligoarthritis (46.6%), followed by enthesitis-related arthritis (ERA; 38.1%). TMJ involvement was diagnosed in 843/2413 patients (34.9%) (677 MRI-confirmed, four not MRI-confirmed, no MRI examination in 162). Female gender (p = 0.017), higher number of additional joints with active arthritis (p < 0.001), anti-nuclear antibody (ANA) positivity (p = 0.005), higher age (p = 0.020), and oligoarthritis (persistent and extended; p = 0.043) were significantly associated with TMJ involvement. Human leucocyte antigen-B27-positive patients were less likely to have TMJ involvement (p = 0.023). Pain on palpation and pain while chewing were statistically significantly associated with TMJ involvement (p = 0.008 and p = 0.020, respectively). Conclusions: Based on our findings, to identify TMJ involvement special attention should be paid to JIA patients with female gender, ANA positivity, and oligoarthritis, as well as those with a higher number of additional joints with active arthritis; and regular examinations of the TMJ should be performed.